Effect of pH and UV exposure on the chromaticity stability of curcumin extracted from temu lawak (Curcuma xanthorrhiza Roxb.) - Abu Bakar, Ainaa Eliah; Othman, Rashidi; Mohd Latiff, Nur Hanie; Ramya, Razanah; Mohd Hatta, Farah Ayuni; Wan Sulaiman, Wan Syibrah Hanisah (Institut Alam dan Tamadun Melayu, UKM, 2025)
The traditional uses of the family Zingiberaceae have a long history and include everything from folk medicine to culinary applications. Numerous ginger species have been the subject of numerous phytochemical, pharmacological, and molecular studies worldwide. Therefore, this study was implemented to explore and investigate in greater depth of curcumin extracted from ginger species in a wide range of rhizome flesh colour. UV-Vis spectrophotometer and CIELAB chromameter were used to measure the curcumin chromaticity stability. The chromaticity stability of curcumin extracted from temu lawak (Curcuma xanthorrhiza Roxb.), as analyzed using the CIELAB colour system, was found to be more stable at lower pH levels (3, 5, and 7) compared to higher pH levels (9 and 11), indicating that acidic to neutral conditions help preserve the colour integrity of curcumin. In addition the curcumin pigment was more stable in UV-B at higher concentrations as compared to UV-A.